Bullous mastocytosis in an infant treated with the help of narrowband ultraviolet B - Parineeta Maria; Sandhya Chauhan; Tanu Agrawal; Pratik Gahalaut (Wolters Kluwer Medknow Publications, 2017)
Mastocytosis represents a group of disorders characterized by abnormal accumulation of mast cells in the bone marrow, liver, spleen, lymph nodes, gastrointestinal tract, and skin. Skin involvement is seen in almost all the cases. A 1-year-old male child presented with complaints of multiple fluid-filled lesions all over the body since 2 months. Examination revealed multiple vesicles and tense bullae present on the face, neck and trunk along with surrounding erythema and multiple excoriation marks. Darier's sign was positive. Histopathology showed dense infiltrates of mast cells in the papillary dermis. Bone marrow aspiration showed no mast cells infiltrate. The patient was started on oral antihistamines, prednisolone, and narrowband ultraviolet B (NBUVB). The skin lesions showed dramatic improvement within a week and patient is on follow-up with NBUVB. Bullous mastocytosis (BM) is a rare variant of cutaneous mastocytosis manifested by diffuse infiltration of skin by mast cells, where cutaneous bullae are the predominant feature. This case is being presented for its rarity and highlights the effectivity of NBUVB for treating BM.